Crisis at Guy's Hospital (1880) and the nature of nursing work. Issue 4 (23rd May 2017) - Tesseyman, Sheri; Hallett, Christine; Brooks, Jane
Abstract : This historical study aims to refine understanding of the nature of nursing work. The study focuses on the 1880 crisis at Guy's Hospital in London to examine the nature and meaning of nursing work, particularly the concept of nursing work as many 'little things.' In this paper, an examination of Margaret Lonsdale's writing offers an original contribution to our understanding of the ways in which nursing work differs from medical practice. In this way, we use the late‐nineteenth‐century controversy at Guy's Hospital as a prism through which to examine the contested nature of nursing work. Lonsdale's ideas are corroborated by examination of writings by nurse leaders Florence Nightingale and Eva Luckes. Luckes, in particular, elaborated what was meant by nursing as the performance of a thousand little things, which are specific to nursing work. While physicians had been performing much of what was considered to be nursing work, nurses developed some of these and other interventions into a unique body of work characterized by meticulous attention to significant details. Some implications regarding current nursing practice are discussed.